Validating a Self-Report Measure of Student Athletes’ Perceived Stress Reactivity: Associations With Heart-Rate Variability and Stress Appraisals - Britton, Darren M.; Kavanagh, Emma J.; Polman, Remco C. J. (Frontiers in Psychology, 2019)
Student athletes experience multiple stressors relating to both their sporting and academic commitments. Individual differences playing a significant role in how well student athletes cope with the demands they face. When assessing individual differences in stress reactivity, there are a lack of valid alternatives to costly and time-consuming lab-based physiological methods (e.g. cortisol sampling, cardiac variables). This paper aims to further validate a self-report measure of adolescent athletes’ individual differences in perceived stress reactivity, by comparing to a psycho-physiological measure of emotion regulation (heart-rate variability) assessed during a socially evaluated cold pressor test. 30 student athletes and 31 student non-athletes completed a measure of perceived stress reactivity and took part in the socially evaluated cold pressor test while their heart-rate variability was assessed, along with their self-reported appraisals of stress, pain, and unpleasantness experienced during the procedure. Controlling for gender and athleticism, individual differences in perceived stress reactivity showed no associations with tonic or phasic levels of heart-rate variability. However, perceived stress reactivity was associated with levels of self-reported stress, pain, and unpleasantness experienced during the socially evaluated cold pressor test. These findings therefore suggest that perceived stress reactivity is associated with cognitive responses to stress (i.e. stress appraisals). However, further research is needed to confirm its relationship with physiological measures and responses. This further adds to the understand of perceived stress reactivity, and validity of the perceived stress reactivity scale for adolescent athletes.